Development and women's reproductive health in Ghana, 1920-1982 - Ashford, Holly, author.
1 online resource (xi, 253 pages)
Keywords: "This book investigates the history of women's reproductive health in Ghana, arguing that between the 1920s and 1980s, it was largely driven by discourses of development and population control, rather than a concern for women's health or rights. Between the 1920s and 1980s, the choices that Ghanaian women made regarding their reproductive health were defined by development policy and practice. Spanning the colonial and immediate postcolonial periods, this book demonstrates that whilst the substance of development discourse shifted over time, principles of development continued to be used to impact and legitimise reproductive health policy and practices well after independence. The book explores Ghana's pluralist health system, the introduction of maternal and child welfare, the dominance of the Red Cross in Ghana's maternal and child health landscape, nationalist pronatalism and global population activism. In order to understand how global iterations of development and health policy impacted on ordinary lives in Ghana, the author uses evidence from multiple 'levels', including private papers, national archives, and records of international and transnational organisations. Providing balanced archival perspectives, the book includes extensive oral history interviews carried out with both rural Ghanaian women and traditional birth attendants, as well as with midwives, doctors and family planning fieldworkers. This book will have an important impact on a number of historical fields including Ghanaian history, global health history, global histories of population and family planning and histories of development. It will be of interest to researchers and students in the history of public health, development, Africa, Ghana and gender"--